Proračun optimalnog perioda zamjene brodske opreme metodom statističkog modeliranja - Mavrić, Ivan (Promet - Traffic&Transportation, 2012)
The article deals with the problem of assessing the optimalvolume and period for the replacement of ship equipment. Theintroduction analyses the character and the volume of technicalmaintenance and the repair of the ship equipment, certainassemblies and elements of that equipment. Possible tasks andvarious ways in which they can be solved are defined. The statisticalmodelling of random processes is particularly stressed.Eventually, the numerical example of statistical modelling oftechnical maintenance and the assessment of the optimal replacementperiod of the ship pump bearing is given.